AGAMA KHONGHUCU PASCA REFORMASI 1998 (STUDI TERHADAP MAKIN YOGYAKARTA) - Haetami Haetami (Religi: Jurnal Studi Agama-agama, 2015)
The highest religious institutions have a decisive role in approaching various religiousphenomena. During the New Order regime, religious institutions are not much presentin the public space since government policy requires society-based organizations underdirect government control. But entering the reformation era in 1998, the variouselements of society began to fi ll public space with various forms of organization,including the MAKIN institution of Confucianism. There are two queries in thispaper, that is how the dynamics of the post-reformation institution for ConfucianReligion in 1998 and how the infl uence of the 1998 reformation on the MAKINYogyakarta. This is a fi eld research with qualitative methods. The data collection wasdone by observation, interview, and documentation. This study uses a phenomenologicalapproach to the analysis of the history and ideology of Louis Althusser’s theory. Theseresults indicate that the dynamics of the post-reformation era in term of institution forConfucian Religion in 1998 experienced a shift towards the better. The establishmentof MAKIN with its chance based on the demanding era has given a signifi cant notefor the followers of Confucianism in general and in particular activists of MAKIN.